2013
DOI: 10.1002/adma.201300176
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Assisted All‐Optical Helicity Dependent Magnetic Switching in Amorphous Fe100–xTbx Alloy Films

Abstract: All-optical switching (AOS) in ferrimagnetic Fe(100-x)Tb(x) alloys is presented. AOS is witnessed below, above, and in samples without a magnetic compensation point. It is found that AOS is associated with laser heating up to the Curie temperature and intimately linked to a low remanent sample magnetization. Above a threshold magnetization of 220 emu/cc helicity dependent AOS is replaced by pure thermal demagnetization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(86 citation statements)
references
References 33 publications
1
77
1
Order By: Relevance
“…The inertial dynamics is also believed to be a key ingredient in the optical manipulation of rare-earth transition-metal ferrimagnets, for example, in GdFeCo (Stanciu et al, 2007), FeTb (Hassdenteufel et al, 2013), and TbCo, DyCo, or HoFeCo (Mangin et al, 2014) alloys. It is however absent in ferromagnets (after an ultrashort field pulse, the magnetization falls back to the lowest energy state).…”
Section: B Optical Manipulationmentioning
confidence: 99%
“…The inertial dynamics is also believed to be a key ingredient in the optical manipulation of rare-earth transition-metal ferrimagnets, for example, in GdFeCo (Stanciu et al, 2007), FeTb (Hassdenteufel et al, 2013), and TbCo, DyCo, or HoFeCo (Mangin et al, 2014) alloys. It is however absent in ferromagnets (after an ultrashort field pulse, the magnetization falls back to the lowest energy state).…”
Section: B Optical Manipulationmentioning
confidence: 99%
“…Thus, AOS may lead to technological breakthroughs by using polarized light for ultrafast magnetization manipulation for a variety of applications. Since this pioneering experimental discovery, AOS has also been demonstrated for a variety of other amorphous ferrimagnetic RE-TM alloys, such as TbFe (Hassdenteufel et al, 2013(Hassdenteufel et al, , 2015Schubert et al, 2014), TbCo (Alebrand et al, 2012), TbFeCo (Finazzi et al, 2013), DyCo , HoFeCo , and just very recently for antiferromagnetically coupled heterostructures Schubert et al, 2014) as well as for ferromagnetic materials . Considerable recent effort has been made to investigate the physics of AOS and to reveal the underlying microscopic mechanisms.…”
Section: Hebler Et Al Ferrimagnetic Tb-fe Alloy Thin Filmsmentioning
confidence: 99%
“…11,[31][32][33][34][35][36] Recently we showed that a minimum amount of laser energy input of the order of the energy gap between the two ferrimagnetic modes, i.e.h∆ω ∼hω ex ∼ J RT (M FeCo (T 0 ) − M Gd (T 0 )), is required for the formation of the TFLS, 11 where ω ex is the frequency of the so-called antiferromagnetic coherent exchange mode. The disordered nature of the GdFeCo spin lattice leads an effect that the most efficient energy transfer (the smallest energy gap) does not correspond exactly to the coherent mode with k = 0 but to non-zero k value, related to the characteristic length of the Gd spins cluster size.…”
Section: B Formation Of the Transient Ferromagnetic Like Statementioning
confidence: 99%